2012
DOI: 10.1186/cc11405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological efficacy of continuous versus intermittent application of meropenem in critically ill patients: a randomized open-label controlled trial

Abstract: IntroductionMeropenem bactericidal activity depends on the time when the free drug concentrations remain above the minimum inhibitory concentration of pathogens. The goal of this study was to compare clinical and bacteriological efficacy of continuous meropenem infusion versus bolus administration in critically ill patients with severe infection, and to evaluate the safety of both dosing regimens.MethodsPatients admitted to the interdisciplinary Intensive Care Unit (ICU) who suffered from severe infections and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 48 publications
7
138
1
3
Order By: Relevance
“…This approach has been recently assessed by several authors for meropenem in the clinical setting (9,22,25,35,40).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been recently assessed by several authors for meropenem in the clinical setting (9,22,25,35,40).…”
Section: Discussionmentioning
confidence: 99%
“…We referred to 4 RCT reports 72, 90, 91, 92. Among these studies, no significant differences were observed between the respective study groups with respect to 90‐day mortality rate (odds ratio: 0.94; 95% confidence interval [CI]: 0.69–1.28, P  =   0.68), ICU mortality rate (odds ratio: 0.79; 95% CI: 0.59–1.06, P  =   0.11), in‐hospital mortality rate (odds ratio: 0.78; 95% CI: 0.59–1.03, P  =   0.08), or target serum drug concentration achievement rate (odds ratio: 1.88; 95% CI: 0.89–3.98, P  =   0.10).…”
Section: Cq5 Antimicrobial Therapymentioning
confidence: 99%
“…A avaliação da eficácia dos métodos de infusão contínua versus infusão intermitente foi variada nos diversos artigos selecionados, variou desde a análise do pico de concentração plasmática do Meropenem, alcance de determinados percentuais da CIM, tempo de concentrações plasmáticas acima do CIM (T >CIM), cura e até mesmo a comparação direta dos dois métodos, também fatores como segurança, perfil farmacocinético, perfil farmacodinâmico e mortalidade (JARURATANASIRIKUL; SRIWIRIYAJAN, 2003;CHYTRA et al, 2012).…”
Section: Discussionunclassified
“…Já no trabalho conduzido por Chytra et al (2012), foi realizada avaliação da eficácia clínica e microbiológica da aplicação de Meropenem por infusão contínua (4 g em 24 horas) em comparação com o método de bolus (2 g durante 30 minutos a cada 8 horas). A cura clínica no fim da terapia com o antibiótico foi comparável para ambos os grupos (83% para o grupo da infusão e 75% para o grupo do bolus; P = 0,180).…”
Section: Discussionunclassified